Brief Reflections on The Obstacles and Solutions Towards Arabic Language Through The Nigerian Literary Ages: A Historical and Descriptive Study - Garba, Ahmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2023)
Arabic language has made important and effective contributions in Nigeria since its emergence and is among the three foreign languages that are officially used higher islamic schools in the country, and it is also in the forefront among the languages taught in major educational institutions in Nigeria, but unfortunately, the language is facing alots of problems and obstacles, which hinder the language from massive development, This paper aims to shed light on the those obstacles and also state some possible solutions and factors that masy help in the growth and development of Arabic language in Nigeria and the extent of its vital contributions to building society. It was noted that the Arabic language is the only language that suffers from cruelty in the hands of orientalists, but it preserves its honor and dignity. Indeed throughout the history of mankind, this language has a great spirit that helps it restore its nobility. This is because in its fold is a great and honorable message, which is the word of God the Mighty.